Social complementary dyads and the subject's resources of success - Vladimir A. Tolochek (Saratov State University, 2022)
The purpose of the article is to describe the phenomenon of "social complementary dyads". Dyads are considered as small social groups (micro groups) being the main forms of people's organization, of culture transfer, and of the development of special knowledge within the professional sphere; as social structures that ensure the reliability and effectiveness of human activity. The author highlighted and analysed the features of the following social complementary dyads (SCD): 'educator - educated', 'teacher - school student', 'lecturer - university student', 'head - subordinate', 'leader - follower', etc. It is believed that varieties of social dyads as the main forms of transmitting social experience of mankind in various professional spheres ('doctor - patient', 'coach - athlete', 'writer - reader', 'consultant - customer', etc.) have historically been increasing. The research presents problematic aspects and difficulties in studying dyads. Hypotheses: 1) the phenomenon of "social complementary dyads" (SCD) is a historically evolving social and psychological phenomenon; 2) social success of the subjects being the partners of a dyad may change in the process of their functioning; 3) purposeful development of unique and specific dyads is possible along with spontaneously developed SCD. The study proposes the typology and describes the features of different social dyads: 1) complementary social dyads (SCD); 2) supportive social formations; 3) professional complex dyads; 4) professional creative dyads; 5) related dyads; 6) spontaneous dyads; 7) destructive (parasitic, exploitative) dyads; 8) asocial dyads. The article discusses correlation between the phenomenon of a 'dyad' and the problem of resources (intra-subject, inter-subject and extra-subject), socio-psychological and psychological mechanisms of actualization, formation and development of resources. The author has identi fied a number of research issues, which have been sufficiently developed in psychology to date and reflect the key features of resources; the issues which can be considered as prototypes for development (problems of integral human individuality; cognitive resources, professional development of the subject, complementarity of qualities of the subjects of joint activity).